The resistance of microorganisms causing urinary tract infection in human and small animals against some antimicrobial agents - Gelaan Sayed Zenhom Saleh; Mona Ibrahim Elenbaawy; Nagwa Sayed Sayed Ata (Cairo : Gelaan Sayed Zenhom Saleh, 2015)
A total of 150 urine samples was collected from dogs, cats and human were examined for enterobacteriaceae by convential methods, and confirmed by rapid API 32E and VITEK - 2 automated system. Vitek 2 was also used to determine the susceptibility of isolates to antimicrobials. Antibiotic susceptibility tests were performed on all positively confirmed isolates. In addition, klebseilla spp. isolates were tested for bla CTX - M genes by PCR. Out of 150 urine samples 86 samples (57.3%) were belonging to enterobacteriaceae. E.coli was the most common prevalent isolate causing UTI (49.8%) followed by Klebsiella spp. (16.4%) then proteus spp. (3.9%) and Pseudomonas spp. (2%). The 58 strains of E. coli isolated were subjected to serogrouping for O antigens. Antibiotic susceptibility tests were performed on all positively confirmed isolates. 62.7% of the isolates, were resistant to three or more different classes of antibiotic agents, and were considered to present MDR. High level of resistance was seen to trimethoprim-sulfamethoxazole, cephalosporins, penicillin, gentamicin. However imipenem was found to be highly sensitive to most urinary isolates of multidrug resistant strains. MDR was found in 48 (82%) of E. coli and in 15 (78%) of Klebsiella spp. isolates and in all (100%) of proteus spp and in all pseudomonas isolates
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Microbiology
Issued also as CD
Keywords: API 32e; Enterobacteriaceae; Urinary tract infections